Implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM) in Sekarsari Florist Surabaya City - Putri, Alifiyah Sindy Maretta; Meldona, Meldona (Jurnal Akuntansi Bisnis, 2024)
This research investigates the challenges faced by small and medium enterprises in preparing financial reports based on SAK-EMKM. Using a qualitative descriptive approach, researchers conducted interviews and field observations of the owners of Sekarsari Florist. The research results show that the MSME Sekarsari Flower Shop in Surabaya City has not implemented SAK-EMKM because the owner of the Sekarsari Flower Shop does not know and understand the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM). Apart from that, they also do not understand the benefits of implementing SAK-EMKM. Obstacles faced by Sekarsari Florist include the lack of socialization and owner knowledge regarding SAK-EMKM. The financial reports prepared by Sekarsari Florist so far are still prepared manually and simply, only in the form of recording cash income from sales and cash disbursements to determine profits and losses in a certain period.